(untitled) (Nuovi Autoritarismi e Democrazie: Diritto, Istituzioni, Società (NAD-DIS), 2021)
The article examines the concepts of authoritarianism and democracy in Turkey through an analysis of academic freedom. From its foundation, Turkish democracy has suffered from being hybrid, i.e., a combination of democratic and authoritarian elements. Since 2016, after the attempted coup d’état, Turkish parliamentarianism has been transformed into a one-man regime. This contribution analyses the new type of Turkish authoritarianism from its foundation, since the rise of Justice and Development Party (AKP), using the Gramscian concept of hegemony and the role of the intellectual. Then, the article presents an interview with a scholar still working in a Turkish university to better understand the state of academic freedom in Turkey.